Efficiency in Cement and Cement Concrete of Dispersed Granitic Rock - A. V. Smolyakov (Наука и техника)
The paper presents results of investigations on the dispersion (grinding) process in a ball mill and it also shows an effect of dispersed granitic rock (granite screenings of RUPP “Granit”, Brest region) used as a mineral additive on cement properties, hardening kinetics and cement stone strength, morphology of cement hydration products in the presence of the granitic rock. Complex studies including data of X-ray phase and derivatographic analyses have revealed that granitic rock material does not change morphology of new formations these are reaction products obtained due to reaction of binder clinker portion with water. They are identical to those that are formed due to reactions of a no-dosage (clean-bite) binder with it. At the same time it has been established that when 10–20 % of granite screening grinded up to Sud ~ 3000 cm2/g (0.3 m2/g) have been added to cement strength of cement stone is increased by 20–25 %, and the amount of chemically bound water in clinker component of the binder is increased by 10–15 %. The paper has substantiated a hypothesis of the “crystallization centers” effect which is revealed by fractions of grinded screening £0.3 μm (£3000 Å). The fractions constitute an amount of ~15 % of the screening mass. This hypothesis has been proved by the above-mentioned data on the increase in cement stone strength and amount of chemically bound water in their presence when samples are hardened in normal-humid conditions, in water and after steaming. There is also an obvious increase in strength of cement stone on a binder with this additive (in 2–2.5 times in 1–3 days of hardening) under conditions of “inhibition” in cement hydration reactions due to introduction of a chemical additive that is lignosulphonate technical additive in the cement paste with enhanced dosage (0.3 % of the cement mass).